Low-value care in Australian public hospitals: prevalence and trends over time. Issue 3 (6th August 2018) - Badgery-Parker, Tim; Pearson, Sallie-Anne; Chalmers, Kelsey; Brett, Jonathan; Scott, Ian A; Dunn, Susan; Onley, Neville; Elshaug, Adam G
Abstract : Objective: To examine 27 low-value procedures, as defined by international recommendations, in New South Wales public hospitals. Design: Analysis of admitted patient data for financial years 2010–2011 to 2016–2017. Main outcome measures: Number and proportion of episodes identified as low value by two definitions (narrower and broader), associated costs and bed-days, and variation between hospitals in financial year 2016–2017; trends in numbers of low-value episodes from 2010–2011 to 2016–2017. Results: For 27 procedures in 2016–2017, we identified 5079 (narrower definition) to 8855 (broader definition) episodes involving low-value care (11.00%–19.18% of all 46 169 episodes involving these services). These episodes were associated with total inpatient costs of A49.9 million (narrower) to A99.3 million (broader), which was 7.4% (narrower) to 14.7% (broader) of the total A674.6 million costs for all episodes involving these procedures in 2016–2017, and involved 14 348 (narrower) to 29 705 (broader) bed-days. Half the procedures accounted for less than 2% of all low-value episodes identified; three of these had no low-value episodes in 2016–2017. The proportion of low-value care varied widely between hospitals. Of the 14 procedures accounting for most low-value care, seven showed decreasing trends from 2010–2011 to 2016–2017, while three (colonoscopy for constipation, endoscopy for dyspepsia, sentinel lymph node biopsy for melanoma in situ) showed increasing trends. Conclusions: Low-value care in this Australian public hospital setting is not common for most of the measured procedures, but colonoscopy for constipation, endoscopy for dyspepsia and sentinel lymph node biopys for melanoma in situ require further investigation and action to reverse increasing trends. The variation between procedures and hospitals may imply different drivers and potential remedies.